Application of polydopamine in biomedical microfluidic devices - Kanitthamniyom, Pojchanun (2019)
Polydopamine (PDA) is a bioinspired material with tremendous potential for applications involving surface modifications. By simply immersing the substrate in the dopamine monomer solution, we are able to apply a hydrophilic and biofunctional PDA coating that adheres strongly to any surface, including (super)hydrophobic surface, with unprecedented ease. Using PDA, almost any materials can be immobilized on the surface in a single step by mixing them with the dopamine monomer solution. This review provides a comprehensive coverage of the applications of PDA in the device fabrication, surface modification, and biofunctionalization of biomedical microfluidic devices. While discussing the advantages and limitations of PDA, we pay special attention to its unique properties that specifically benefit biomedical microfluidic devices. We also discuss other potential applications of PDA beyond the current development. Through this review, we hope to promote PDA and encourage a broader adoption of PDA by the microfluidic community.